The raft [videorecording (DVD)] - Giménez Cacho, Daniel; Genovés, Santiago; Seymour, Fe; Bjornstam, Maria (Kino Lorber, 2020)
In the summer of 1973, a young international crew of six women and five men embarked together on a most unusual sea voyage, a close-quarters trip across the Atlantic from Spain to Mexico on a free-floating raft christened the Acali, initiated by Mexican anthropologist Santiago Genoves, who proposed to use the group as guinea pigs in his investigation of the origins of violent conflictand dynamics of sexual attraction.